Price setting during the coronavirus (COVID-19) pandemic - Lukas Henkel; Elisabeth Wieland; Aneta B±açzejowska; Cristina Conflitti; Brian Fabo; Ludmila Fadejeva; Jana Jonckheere; Peter Karadi; Pawe± Macias; Jan-Oliver Menz; Pascal Seiler; Karol Szafranek (European Central Bank (ECB), 2023)
The coronavirus (COVID-19) pandemic caused a deep recession globally, as well as in the euro area, accompanied by a steep decline in inflation rates in 2020. This paper reviews some of the main challenges created by the pandemic for inflation measurement and provides micro price data analysis of how price setting has reacted to the strong COVID-19 shock. For this purpose, we use three different, but complementary, microdata sources for specific countries and sectors: micro price data underlying the official consumer price indices in Germany, Italy, Latvia and Slovakia; (scanner) data from German and Italian supermarkets; and online (webscraped) prices for Poland. A common finding of the micro price studies in this paper is that state dependence significantly contributed to the price-setting response to the COVID-19 shock. Nevertheless, the extent and degree of responses varies widely by sector and even country, also depending on the severity of the pandemic situation.
Keywords: D4; E31; 330; price rigidity; inflation; consumer prices; heterogeneity; microdata; COVID-19